Correction: the influence of age and sex on genetic associations with adult body size and shape: a large-scale genome-wide interaction study - Winkler, T; Justice, A; Graff, M; Barata, L; Feitosa, M; Chu, S; Czajkowski, J; Esko, T; Fall, T; Kilpeläinen, T; Lu, Y; Mägi, R; et al. (Public Library of Science, 2016)
[This corrects the article DOI: 10.1371/journal.pgen.1005378.].